Investigating hope in oral health promotion for adolescents: an exploratory study based on observations at the dental clinic - Jasbi, Arefe; Sand, Kari; Marshman, Zoe; Høiseth, Marikken (Frontiers in Oral Health, 2024)
Introduction Maintaining well-being is crucial, especially in challenging conditions, considering the common public health issue of dental caries. Within the context of adolescent oral health, this research explores the techniques employed by dental professionals to potentially foster hope -a positive manner that promotes well-being- in adolescents during consultations, opening a window into the realm of patient engagement and well-being. Materials and methods Data were collected through observations conducted at public dental clinics in Norway, with the participation of three dental professionals and four adolescents between the ages of 12 and 15 years. The data were analyzed using thematic analysis. Practices were observed from dental professionals in their interactions with adolescents, which align with features of hope. Result Three core themes were identified: (1) bonding strategies; (2) verbal and non-verbal strategies for creating positive relationships; and (3) adolescents' empowerment in dental consultations. Conclusion Although a new concept within oral health promotion, it seems that dental professionals in this study were observed to be facilitating hope in adolescents when they were providing their dental care. Consideration should be given to the potential for future approaches to be developed for use in dental consultations to facilitate hope strategically. While these approaches are likely to contribute to improving patient-centredness, consideration is needed of challenges and barriers to their implementation.